ZnO/CdS/CuS heterostructure: A suitable candidate for applications in visible-light photocatalysis. (January 2022) - Nandi, Prami; Das, Debajyoti
Abstract: To eliminate the coloured-elements/dyes from effluents, ZnO based photocatalysts are significantly effective. Using simple low temperature aqueous solution process ZnO/CdS/CuS ternary heterostructure has been developed, wherein CdS and CuS nanoparticles are embedded onto the surface of micron-sized ZnO hexagonal disks, the morphology and chemical composition of which are determined by X-ray diffraction, transmission electron spectroscopy and X-ray photoelectron spectroscopy. The CdS and CuS nanoparticles on the ZnO surface play crucial roles in substantial reduction of the optical band gap that facilitates in a significant visible light photocatalysis characteristics of the heterostructure. An enlarged surface area of the heterostructure contributes increased number of reactive sites for dye adsorption. Besides the synergistic effect, the optimized band structures of ZnO, CdS and CuS strategically influence on the effective electron-hole separation and transfer. Efficient photocatalytic dye degradation is accomplished via formation of the superoxide radicals (O2 − ) by the CB-electrons and the hydroxyl radicals (OH) by the VB-holes. For ZnO/CdS/CuS heterostructures superior photocatalytic activity with the highest degradation rate constants 'k', ~0.0152 min −1 for RhB dye and 0.0217 min −1 for MO dye are obtained via strategically impeding the recombination of photoexcited charge carriers by proper band alignment among different components of the heterostructure. Graphical abstract: Image 1 Highlights: ZnO/CdS/CuS heterostructure with CdS/CuS NPs embedded onto micron-sized ZnO hexagonal disk, grown via low temperature aqueous solution process. CdS/CuS NPs on ZnO surface facilitate visible light absorption, enlarged surface area provides surplus reactive sites for dye adsorption. Besides synergistic effect, optimized band structures of ZnO/CdS/CuS strategically influence on effective e – /h + separation and transfer. Efficient photocatalytic dye degradation accomplished via formation of superoxide (O2 − ) and hydroxyl (OH) radicals Noble metal free ZnO/CdS/CuS photocatalyst attains superior activity with high rate constants ~0.0152 min −1 for RhB and 0.0217 min −1 for MO dye.